THE ROLE OF HIGHER EDUCATION POLICY AND THE DEVELOPMENT OF MANAGEMENT SCIENCE IN THE INDUSTRIAL REVOLUTION 4.0: A PERSPECTIVE FROM INDONESIA - Yudha Dwi Nugraha (Academy of Education Journal, 2021)
The development of digital technology has disrupted a variety of human activities, not only as a driving force for the economy but also in the fields of science and technology and higher education. The industrial revolution 4.0 era has influenced higher education policy, teaching, and development of management science in universities. This article focuses to discuss the role of higher education policy and the development of management science in the era of industrial revolution 4.0. Based on theoretical studies and relevant literature reviews, the author argued that the challenges of the industrial revolution 4.0 must be responded quickly and appropriately by all stakeholders to be able to anticipate changes in the world and increase the competitiveness of the Indonesian college student in the midst of global competition. The management science curriculum development must emphasize the fields of Science, Technology, Engineering, and Mathematics. Management science should refer to learning based on information and communication technology, the internet of things, big data, and computerization. Furthermore, management science is expected to create higher thinking order skills (HOTS) for higher education students. Finally, management science is also expected to provide teaching and have noble values, spiritual values, wisdom, and the element of human touch.